Estimation of measles reproduction ratios and prospects for elimination of measles by vaccination in some Western European countries. - Wallinga, J. (Cambridge University Press, 2001)
The objective of this study is to estimate the measles reproduction ratio for eight Western European vaccination programmes. Because many plausible age-structured transmission patterns result in a similar description of the observations, it is not possible to estimate a unique value of the reproduction ratio. A method is developed to estimate bounds and confidence intervals for plausible values of the reproduction ratios using maximum likelihood methods. Lower and upper bounds for plausible values of the basic reproduction ratio are estimated to be 7.17 (95% CI 7.14-7.20) and 45.41 (95% CI 9.77-49.57), corresponding to lower and upper bounds on critical vaccine coverage of 86.6% and 98.1%. Of the eight evaluated vaccination programmes, four have vaccine coverage below the lower bound and allow measles to persist, and four have vaccine coverage at the upper bound and may eventually eliminate measles.